2016
DOI: 10.1039/c6ce01535b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and mechanism of a novel direct solid-state Z-scheme photocatalyst CdS/BiOI under visible light

Abstract: A direct CdS/BiOI Z-scheme heterojunction has been successfully synthesized via a hydrothermal method for the first time. The photocatalytic performances of as-prepared samples were evaluated by rhodamine B degradation under visible light (λ > 420 nm) irradiation. The phase structures, morphologies and optical properties of the obtained samples were investigated by several characterization tools such as XRD, SEM, TEM, HRTEM, STEM, XPS, and UV-vis, photocurrent and PL spectroscopy. The results revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…A typical case is CdS/BiOI photocatalyst, which was evaluated by RhB degradation . In this work, EDTA‐2Na, K 2 CrO 7 , isopropanol (IPA) and p‐benzoquinone (BQ) were respectively used for trapping holes, electrons, .…”
Section: Evidence Of Z‐scheme Mechanismmentioning
confidence: 99%
“…A typical case is CdS/BiOI photocatalyst, which was evaluated by RhB degradation . In this work, EDTA‐2Na, K 2 CrO 7 , isopropanol (IPA) and p‐benzoquinone (BQ) were respectively used for trapping holes, electrons, .…”
Section: Evidence Of Z‐scheme Mechanismmentioning
confidence: 99%
“…Many previous studies have shown that metal oxide/chalcogenide semiconductors play an important part in the photocatalytic process. [12][13][14][15][16] However, for now, there are still challenges regarding the large-scale construction of recyclable photocatalytic materials through mild methods.…”
mentioning
confidence: 99%
“…Moreover, the EDS and elemental mapping analysis [Fig. (c–f)] demonstrates that the Bi, W and O elements are homogeneously distributed on the surface of flower‐like microsphere, which explicitly demonstrates that the as‐prepared sample is Bi/Bi 2 WO 6 composite catalyst …”
Section: Resultsmentioning
confidence: 92%